One Bout of Aerobic Exercise Can Enhance the Expression of Nr1d1 in Oxidative Skeletal Muscle Samples - Rovina, Rafael L.; da Rocha, Alisson L.; Marafon, Bruno B.; Pauli, José R.; de Moura, Leandro P.; Cintra, Dennys E.; Ropelle, Eduardo R.; da Silva, Adelino S. R. (Frontiers in Physiology, 2021)
The nuclear receptor subfamily 1, group D member 1 (Nr1d1), plays a role in the skeletal muscle's oxidative capacity, mitochondrial biogenesis, atrophy genes, and muscle fiber size. In light of the effects of physical exercise, the present study investigates the acute response of Nr1d1 and genes related to atrophy and mitochondrial biogenesis on endurance and resistance exercise protocols. In this investigation, we observed, after a bout of endurance exercise, an upregulation of Nr1d1 in soleus muscle, but not in the gastrocnemius, and some genes related to mitochondrial biogenesis and atrophy were enhanced as well. Also, analysis of muscle transcripts from diverse isogenic BXD mice families revealed that the strains with higher Nr1d1 gene expression displayed upregulation of AMPK signaling and mitochondrial-related genes. In summary, a single session of endurance exercise can enhance the Nr1d1 mRNA levels in an oxidative muscle.